Effects of vagotomy on cardiovascular and heart rate variability alterations following chronic normobaric hypoxia in adult rabbits - Alcayaga, Julio; Del-Rio, Rodrigo; Moya, Esteban A.; Freire, Matías; Iturriaga, Rodrigo (My University, 2018)
Abstract Background: chronic hypoxia increases basal ventilation and pulmonary vascular resistance, with variable changes in arterial blood pressure and heart rate, but it's impact on heart rate variability and autonomic regulation have been less well examined. We studied changes in arterial blood pressure, heart rate and heart rate variability (HRV) in rabbits subjected to chronic normobaric hypoxia (CNH; PB ~ 719 mmHg; FIO2 ~ 9.2%) for 14 days and assess the effect of autonomic control by acute bilateral vagal denervation. Results: exposure to CNH stalled animal weight gain and increased the hematocrit, without affecting heart rate or arterial blood pressure. Nevertheless, Poincaré plots of the electrocardiographic R-R intervals showed a reduced distribution parallel to the line of identity, which interpreted as reduced long-term HRV. In the frequency domain, CNH reduced the very-low- (< 0.2 Hz) and high-frequency components (> 0.8 Hz) of the R-R spectrograms and produced a prominent component in the low-frequency component (0.2-0.5 Hz) of the power spectrum. In control and CNH exposed rabbits, bilateral vagotomy had no apparent effect on the short- and long-term HRV in the Poincaré plots. However, bilateral vagotomy differentially affected higher-frequency components (> 0.8 Hz); reducing it in control animals without modifying it in CNH-exposed rabbits. Conclusions: These results suggest that CNH exposure shifts the autonomic balance of heart rate towards a sympathetic predominance without modifying resting heart rate or arterial blood pressure.
Keywords: heart rate variability; chronic normobaric hypoxia; cardiovascular regulation; sympathetic control; vagal activity; poincaré plot; spectral components